Pengembangan Modul Pembelajaran Berbasis Problem Based Learning Untuk Pemahaman Konsep Fisika Pembelajar Siswa Kelas X SMK - Lis Suswati; Yus'iran Yus'iran; Muhammad Subhan; Hermansyah Hermansyah (GRAVITY EDU : Jurnal Pembelajaran dan Pengajaran Fisika, 2022)
A module is a teaching material that is arranged systematically in language that is easily understood by students according to their level of knowledge and age, so that they can learn on their own (independently) with minimal assistance or guidance from educators. Problem Based Learning helps to show and clarify ways of thinking and the richness of the cognitive structures and processes involved in them. This research is a development research (R&D) with a 4-D model, namely: define, design, develop, and disseminate. The product produced in this development research is a physics module based on Problem Based Learning on quantity and unit material. Field trials on class X students of SMKN 2 Wera. The research instrument used in this study is by using a questionnaire with a total of 15 questions. Based on the results of the study, it shows that: (1) the Physics module based on Problem Based Learning produced is feasible to use for Understanding Physics Learning Concepts with an average score of 4.3 in the "very good" category, (2) the use of PBL based physics modules on material the size and unit of understanding the concept of physics students in class X SMKN 2 Wera in field trials with an average score of 4.2 in the "very good" category.